Strategi Pengembangan Usaha Perkebunan Kelapa Sawit Mandiri di Kecamatan Anggaberi Kabupaten Konawe - Hapriadin Samsu Pagala; Sarty Syarbiah; Milawati Saranani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to analyze the strategy of developing oil palm plantation business in Andabia Village, Anggaberi District, Konawe Regency. The number of research samples was 26 people. To answer the research objectives using SWOT analysis. The strategy implemented by farmers in developing oil palm business in Andabia Village is in quadrant 1 (one), which is a situation where oil palm farmers have internal strength and also have many opportunities. Therefore, oil palm farmers must use and utilize their internal strengths to the maximum and take advantage of existing opportunities. The right strategy is to use strength to take advantage of large long-term opportunities, namely with an aggressive strategy.